Level of Acceptability of Carrot Pandesal (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
Filipino love to eat and discover new kinds of food. Filipinos believe that eating is the best way to release their stress and other problems. Among the most famous foods for Filipinos are street foods. Therefore, the researchers came up with the idea of establishing a business that is high in demand and can be easily accepted in the market. Carrot pandesal is a business that produces quality food that is healthy and affordable. It is also highly in demand because of its unique and delicious taste. The researchers used a survey questionnaire to know the levels of satisfaction and acceptability among the respondents. The researchers distributed the questionnaires to random respondents, and the answers will be tallied by the proponents. According to the results of the survey conducted by the researchers, 3.9% of the respondents very strongly agreed to carrot pandesal and 3.8% of the respondents strongly agreed. In terms of pricing, 4.5% of the respondents chose Php 2. A total of 3.9% of the respondents prefer the appearance of carrot pandesal. In terms of the satisfaction of the respondents regarding carrot pandesal, 3.9% of the respondents very strongly agreed. Meanwhile, in terms of pricing, 4.5% of the respondents chose Php 2 as their standard retail price. Considering that the trends in society are changing, and the rates of related health problems are increasing, this procedure can be used at a commercial level. Therefore, the researchers chose a healthy product.
Keywords: tallied, appearance